Measuring what the world eats: Insights from a new approach - Beal, Ty; Herforth, Anna; Kennedy, Gina; Manners, Rhys; Adewopo, Julius; Manguene, Catia; Nhambire, Roberto (Global Alliance for Improved Nutrition, 2022)
Diet quality is critical for human health. Current diets are the main drivers of ill health and premature mortality, with negative spillover effects on the environment and economy. Monitoring diet quality globally is thus essential for holding decision makers accountable for progress toward global nutrition, health, and development goals. Yet there has been no way of monitoring diet quality in a credible, affordable, and timely way. Gallup, Harvard University, and the Global Alliance for Improved Nutrition teamed up to overcome this challenge by initiating the Global Diet Quality Project. Through this project we have created a new approach that enables countries to track diet quality year to year, seasonally, or even more frequently. The new approach allows users to investigate both people’s overall dietary adequacy and their consumption of foods that protect against or increase risk for noncommuni-cable diseases (NCDs). The project has worked with the Gallup World Poll data collection platform to provide the first round of diet quality data from 2021 for 41 countries, representing two-thirds of the world’s population. The project aims to collect data for 140 countries in the future.